Mass food challenges in a vacant COVID‐19 stepdown facility: Exceptional opportunity provides a model for the future. Issue 8 (28th July 2021) - Byrne, Aideen M.; Trujillo, Juan; Fitzsimons, John; Mohammed, Tariq; Ghent, Robert; O'Carroll, Cathryn; Coghlan, David; Hourihane, Jonathan O'B; Alsalemi, Ali; Cassidy, Aoife; Corbet, Eva; Creighton, Rita; et al.
Abstract: Background: Internationally, the COVID‐19 pandemic severely curtailed access to hospital facilities for those awaiting elective/semi‐elective procedures. For allergic children in Ireland, already waiting up to 4 years for an elective oral food challenge (OFC), the restrictions signified indefinite delay. At the time of the initiative, there were approx 900 children on the Children's Health Ireland (CHI) waiting list. In July 2020, a project was facilitated by short‐term (6 weeks) access to an empty COVID stepdown facility built, in a hotel conference centre, commandeered by the Health Service Executive (HSE), Ireland. The aim of this study was to achieve the rapid roll‐out of an offsite OFC service, delivering high throughput of long waiting patients, while aligning with existing hospital policies and quality standards, international allergy guidelines and national social distancing standards. Methods: The working group engaged key stakeholders to rapidly develop an offsite OFC facility. Consultant paediatric allergists, consultant paediatricians, trainees and allergy clinical nurse specialists were seconded from other duties. The facility was already equipped with hospital beds, bedside monitors (BP, pulse and oxygen saturation) and bedside oxygen. All medication and supplies had to be brought from the base hospital. Daily onsite consultant anaesthetic cover was resourced and a resuscitation room equipped. Standardized food challenge protocols were created. Access to the onsite hotel chef facilitated food preparation. A risk register was established. Results: After 6 weeks of planning, the remote centre became operational on 7/9/2020, with the capacity of 27 OFC/day. 474 challenges were commenced: 465 (98%) were completed and 9 (2%) were inconclusive. 135 (29%) OFCs were positive, with 25 (5%) causing anaphylaxis. No child required advanced airway intervention. 8 children were transferred to the base hospital. The CHI allergy waiting list was reduced by almost 60% in only 24 days. Conclusions: Oral food challenges remain a vital tool in the care of allergic children, with their cost saving and quality‐of‐life benefits negatively affected by a delay in their delivery. This project has shown it is possible to have huge impacts on a waiting list efficiently, effectively and safely with good planning and staff buy‐in—even in a pandemic. Adoption of new, flexible and efficient models of service delivery will be important for healthcare delivery in the post–COVID‐19 era. Abstract :